PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHDAP LIKUIDITAS KOPERASI NTALA GEWANG - de Robert, Chrispianus Paulo; Amtiran, Paulina Y; Foenay, Christien C; Ndoen, Wehelmina M (GLORY Jurnal Ekonomi dan Ilmu Sosial, 2023)
This research was conducted with the aim of determining cash turnover and receivables turnover against the liquidity level of the Ntala Gewang Cooperative.The data used is secondary data in the form of financial statements of the Ntala Gewang Cooperative from 2017 to 2021.The data was analyzed using multiple linear regression equations. The results showed that partially cash turnover had a significant effect on the liquidity of the Ntala Gewang Cooperative and partially the turnover of receivables had a significant effect on the liquidity of the Ntala Gewang Cooperative.Simultaneously cash turnover and receivables turnover had a significant effect on the liquidity of the Ntala Gewang Cooperative.